Lack of Association Between Helicobacter pylori Infection and the Risk of Thyroid Nodule Types: A Multicenter Case-Control Studyin China - Wang, Xiao-Song; Xu, Xi-Hai; Jiang, Gang; Ling, Yu-Huan; Ye, Tian-Tian; Zhao, Yun-Wu; Li, Kun; Lei, Yu-Ting; Hu, Hua-Qing; Chen, Ming-Wei; Wang, Heng (Frontiers in Cellular and Infection Microbiology, 2021)
The prevalence of Helicobacter pylori (H. pylori) infection is high worldwide, and the research on the relationship between H. pylori infection and extra-gastric diseases have been concerned. Although H. pylori infection may be involved in thyroid diseases, including thyroid nodule (TN), the association has mainly been explored on potential physiological mechanisms in previous studies, and has not been validated by large population epidemiological investigations. We thus conducted a case-control study and evaluated participants who received regular health examination from 2017 to 2019. The classification of cases and controls was defined by ultrasound diagnosis, and the TN types were classified by American College of Radiology (ACR) TI-RADS. H. pylori infection was determined by C14 urea breath test. Binary and ordinal logistic regression were conducted to verify the relationship between H. pylori infection and TN risk as well as severity. Finally, a total of 43411 participants were recruited, including 13036 TN patients and 30375 controls. Compared with H. pylori non-infection group, the crude OR was 1.07 in Model 1 (95% CI=1.03-1.14) without adjustment, but the results were negative in Model 2 (OR=1.02, 95% CI=0.97-1.06) adjusted for gender, age, BMI, blood pressure and Model 3 (OR=1.01, 95% CI=0.97-1.06) adjusted for total cholesterol, triglyceride, low density lipoprotein, high density lipoprotein on the basis of Model 2. The control variables, including gender, age, BMI and diastolic pressure were significantly associated with TN risk. Ordinal logistic regression showed a positive correlation between H. pylori infection and malignant differentiation of TN (Model 1: OR=1.06, 95% CI=1.02-1.11), but Model 2 and Model 3 also showed negative results (Model 2: OR=1.01, 95% CI=0.96-1.06; Model 3: OR=1.01, 95% CI=0.96-1.05). In conclusion, there is no association between H. pylori infection and TN risk as well as the severity of its malignant differentiation. This study provides important information for correcting possible misconceptions about the pathogenesis of TN and optimizing health guidance for this common thyroid disease.